A comparative study of relationship satisfaction in dating and friends with benefits among emerging adults - Faqih Azka Ash Shidqi; Woro Apriliana Sari (Empathy : Jurnal Fakultas Psikologi, 2025)
Recent shifts in romantic relationship dynamics among emerging adults have contributed to the increasing prevalence of diverse relationship forms,  including dating relationships and friends with benefits (FWB). Examining how these relationship structures relate to relationship satisfaction is essential for understanding contemporary romantic experiences. This study aimed to compare levels of relationship satisfaction between individuals engaged in dating relationships and those involved in FWB relationships. Employing a quantitative comparative design with a non-equivalent group approach,  data were collected from 136 emerging adults aged 20-25 years through an online survey utilizing the Relationship Assessment Scale (RAS) developed by Hendrick. Participants were recruited using purposive sampling,  and group differences were examined using an independent samples t-test. The results revealed a significant difference in relationship satisfaction,  with individuals in dating relationships reporting higher satisfaction levels than those in FWB relationships (p < .05). These findings highlight the critical role of emotional intimacy and commitment in fostering satisfying romantic relationships. The study contributes theoretically by extending the understanding of non-traditional relationship dynamics within the Indonesian cultural context and offers practical implications for counselors,  sex educators,  and developmental psychologists in supporting emerging adults’ navigation of romantic relationships.